2018
DOI: 10.1101/329052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenome-wide association analysis of LDL-cholesterol lowering genetic variants in PCSK9

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…Although there is no evidence on the effects of PCSK9 inhibitors in cancerous conditions, recent studies have shown that PCSK9 variants with LDL-lowering mutations mimicking PCSK9 inhibitors are associated with a lower risk and occurrence of cancer [36,54]. Such inconsistency between results of our study and others is probably due to different modalities of PCSK9 inhibition.…”
Section: Discussioncontrasting
confidence: 94%
“…Although there is no evidence on the effects of PCSK9 inhibitors in cancerous conditions, recent studies have shown that PCSK9 variants with LDL-lowering mutations mimicking PCSK9 inhibitors are associated with a lower risk and occurrence of cancer [36,54]. Such inconsistency between results of our study and others is probably due to different modalities of PCSK9 inhibition.…”
Section: Discussioncontrasting
confidence: 94%
“…The moderate anti-tumor effect of the tested anti-PCSK9 vaccine is underpinned by the recent Mendelian randomization study which revealed that LDL-lowering mutations of PCSK9 mimicking PCSK9 inhibitors were correlated with a lower risk of breast cancer occurrence, while PCSK9 with LDL-raising mutations has a causal correlation with a higher risk of breast cancer [26]. It is further supported by another human study analyzing a phenome-wide association of LDL-lowering genetic variants in the PCSK9 locus mimicking PCSK9 inhibitors, showing that these PCSK9 variants do not increase the risk of cancer [39]. However, a prospective, population-based cohort study showed that there is no association between LDL-lowering PCSK9 polymorphisms and the risk of cancer [25].…”
Section: Discussionmentioning
confidence: 79%
“…Understanding which proteins influence which diseases is a fundamental problem in biomedical science since proteins are the major biological effector molecules. Proteins are also the targets of most medicines, so interest has emerged in the use of MR approaches to identify and validate drug targets [21][22][23][24] . Moreover, recent technological developments enable measurement of hundreds or thousands of proteins on an -omics scale in a single biological sample 8 .…”
Section: Introductionmentioning
confidence: 99%